PENINGKATAN KUALITAS HIDUP SISWA SMKN 1 LELEA KABUPATEN INDRAMAYU DALAM MENGATASI STRES PERKEMBANGAN MASA REMAJA - Denrich Suryadi; Julyarno Chandra; Mikaella Audrey; Natasya Alodia; Cyindy Mulapoa; Andini Dwininta (Jurnal Bakti Masyarakat Indonesia, 2022)
SMKN 1 Lelea, which is located in area of Nagrak, Taman Sari Village, consists of 1,461 students who live in theLelea sub-district, Indramayu district. Counseling teacher team that handles the students of SMKN 1 needs help toprovide education about dealing with adolescent stress related to academic problems, personal/family problems andadolescent problems in general. The purpose of this PKM program is to provide psychoeducation about the stress ofadolescent development and how to deal with stress ef ectively. The current target of PKM is for students of SMKN 1Lelea class X, amounting to 461 people. The Project MBKM group in the Village that helps SMKN 1 Leleaconducted a survey on February 23, 2022 and designed two activities, namely psychoeducational activities on howstudents are able to cope with various stresses faced during adolescent development on March 21, 2022 andcounseling activities. peer group for class X students of SMKN 1 Lelea who need personal counseling which willtake place on March 24-30, 2022. The result of this activity is an increase in knowledge about stress, its impact andpractical ways of dealing with stress on adolescent development in students of SMKN 1 Lelea class X who areattended by 130 participants. While peer counseling activities were also attended by 17 students with feedback in theform of feeling calmer. relieved, happy, more motivated, less stressed, more able to introspect, open to problems andfeelings, increase knowledge, and get more support from the counseling process. ABSTRAK: SMKN 1 Lelea yang terletak di dusun Nagrak, Desa Taman Sari memiliki 1.461 siswa yang berdomisili dikecamatan Lelea kabupaten Indramayu. Tim guru BK SMKN 1 Lelea membutuhkan bantuan untuk memberikanedukasi mengenai penanganan stres remaja terkait dengan masalah akademik, masalah pribadi/keluarga dan masalahremaja pada umumnya. Tujuan program PKM ini untuk memberikan psikoedukasi mengenai stres perkembanganmasa remaja dan cara efektif mengatasi stres. Sasaran PKM saat ini pada siswa SMKN 1 Lelea kelas X yangberjumlah 461 orang. Kelompok MBKM Proyek di Desa yang membantu SMKN 1 Lelea telah melakukan surveipada tanggal 23 Februari 2022 dan merancang dua buah kegiatan yaitu kegiatan psikoedukasi mengenai bagaimanacara siswa/i mampu mengatasi berbagai stres yang dihadapi dalam masa perkembangan remaja pada tanggal 21Maret 2022 dan kegiatan konseling sebaya bagi siswa kelas X SMKN 1 Lelea yang membutuhkan konseling secarapribadi yang berlangsung pada tanggal 24-30 Maret 2022. Hasil kegiatan ini adalah bertambahnya pengetahuanmengenai stres, dampak dan cara praktis mengatasi stres perkembangan remaja pada siswa/i SMKN 1 Lelea kelas Xyang diikuti oleh 130 orang peserta. Hasil pre-test dan post-test untuk menunjukkan perbedaan pengaruh informasidalam seminar terlihat perubahan yang signifikan. Sedangkan kegiatan konseling sebaya juga diikuti oleh 17 orangsiswa dengan umpan balik berupa perasaan lebih tenang. lega, senang, lebih termotivasi, tidak tertekan, lebihmampu introspeksi diri, terbuka dengan masalah dan perasaan, menambah pengetahuan, dan mendapatkan lebihbanyak dukungan dari proses konseling tersebut.